Identifying blast trauma in the human skeleton: applications for forensic anthropology - Márquez-Grant, Nicholas; Webster, Hannah; Dussault, Marie-Christine; Harris, Michael; Roberts, Julie; Errickson, David; Sanabria Medina, César (Archaeopress, 2021)
Trauma analysis is an integral part of the forensic anthropologist’s role in the study of skeletonized human remains. An increasingly common type of injury, however, remains vastly unexplored in the anthropological literature: blast injury. This chapter aims to provide more information on how blast injury can present in the human skeleton, offering the beginning of a guide for anthropologists looking to identify this type of trauma. The study was done by reviewing publications that detail trauma observed in victims of explosive incidents and extracting data on skeletal trauma from a forensic anthropology perspective by calculating the prevalence of these injuries. Overall, the effects of blast were noted to affect nearly every part of the skeleton when the data was reviewed in combination.
Keywords: blast trauma; forensic anthropology; explosion; conflict; human skeleton